2015
DOI: 10.1111/bju.12749
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surgeon volume on the morbidity and costs of radical cystectomy in the USA: a contemporary population‐based analysis

Abstract: ObjectivesTo evaluate the relationship between surgeon volume of radical cystectomy (RC) and postoperative morbidity, and to assess the economic burden of bladder cancer in the USA. MethodsWe captured all patients who underwent RC (International Classification of Diseases, ninth revision, code 57.71) between 2003 and 2010, using a nationwide hospital discharge database. Patient, hospital and surgical characteristics were evaluated. The annual volume of RCs performed by the surgeons was divided into quintiles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 50 publications
(66 reference statements)
1
67
0
Order By: Relevance
“…4 These factors have contributed to the centralization of care to high-volume providers for a number of complex procedures. 14 Our study demonstrated that when radical cystectomy was performed, greater than 90% of patients also underwent a pelvic lymph node dissection. This suggests that if a radical cystectomy is performed, then the vast majority of patients are appropriately undergoing a pelvic lymph node dissection.…”
Section: Discussionmentioning
confidence: 62%
“…4 These factors have contributed to the centralization of care to high-volume providers for a number of complex procedures. 14 Our study demonstrated that when radical cystectomy was performed, greater than 90% of patients also underwent a pelvic lymph node dissection. This suggests that if a radical cystectomy is performed, then the vast majority of patients are appropriately undergoing a pelvic lymph node dissection.…”
Section: Discussionmentioning
confidence: 62%
“…17,18 Multivariate regression modeling was used to compare rates of each complication across the 3 groups after adjusting for age and comorbidities. The Elixhauser method was chosen to adjust for patient comorbidities 19 as it is incorporated into the NIS and performs favorably compared to other indices.…”
Section: Outcomes and Statistical Analysismentioning
confidence: 99%
“…It has been shown, that in centres where RC is performed less frequently than 50/year, the complication rate is statistically higher than in centers where RC is performed routinely [36]. It has been demonstrated in another paper, that when compared with surgeons performing one RC annually, surgeons performing ≥7 RCs each year had 45% lower odds of major complications [37]. Likewise, significantly improved RC results are observed in residency teaching institutions and in large centers specializing in oncology compared with other centers [38].…”
Section: Methodsmentioning
confidence: 99%